Flavonoid compound from Forsythia suspensa leaves inhibits adenovirus infection related to cell cycle based on UHPLC-Q-Exactive-Orbitrap/MS and experimental validation - Wang, Lingling; Ren, Shuanshan; Ma, Xingming; Li, Yanliu; Zheng, Yongyong; Li, Ling; Cao, Luhong (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionForsythia suspensa leaves (FSL), a traditional Chinese ethnomedicinal herbal material used to prepare health-promoting infusions and pharmacologically noted for their robust anti-inflammatory, antioxidant, and broad-spectrum antiviral activities, nevertheless have an as-yet-uncharacterized molecular mechanism of action against human adenovirus (HAdV).MethodsUltra-high-performance liquid chromatography coupled with Q-Exactive Orbitrap mass spectrometry (UHPLC-Q-Exactive-Orbitrap/MS) was employed to identification of FSL components. Publicly available GEO datasets were mined to identify HAdV-associated differentially expressed genes (DEGs). An integrated analysis of GEO datasets and network pharmacology to predict the key molecular targets of FSL flavonoids against HAdV. Ensemble molecular docking and molecular dynamics simulations assessed the stability of flavonoid–protein interactions. In vitro antiviral assays quantified FSL’s effect on HAdV replication, viral gene expression, and E1A protein levels. Flow cytometry and RT-qPCR examined cell cycle distribution and expression of cell-cycle regulators.ResultsThirty-nine active components were identified in FSL, predominantly organic acids, terpenoids, flavonoids, and lignans. An integrated analysis of GEO data revealed 990 adenovirus-associated DEGs, with network pharmacology and functional enrichment analyses further demonstrating FSL flavonoids’ preferential targeting of cell cycle regulators. In silico docking and simulation confirmed the stable binding of FSL-derived flavonoids to core cell cycle proteins. In vitro, FSL inhibited HAdV replication in a dose-dependent manner, significantly reducing viral gene transcripts and E1A protein expression. Mechanistic studies demonstrated that FSL induced G2/M phase arrest, accompanied by the downregulation of CDC25A expression and upregulation of CCNB2, AURKA, CHEK1, and CCNA2 expression, thereby blocking progression into S-phase and impairing viral DNA synthesis.DiscussionThese findings establish a pharmacological foundation for developing FSL-derived phytotherapeutics against adenoviral infections.